Analysis of caesarean sections using Robsons classification system in a tertiary centre at CIHSR, Dimapur, Nagaland, India - Bendangtoshi Jamir; Kanili Jimo; Rebeki Momin (New Indian Journal of OBGYN)
Objectives: The objectives of the study were to assess the rate of caesarean section rate and analysis the caesarean sections using Robson’s TGCS. Methods: A retrospective cohort study was done at CIHSR, Dimapur, Nagaland using total enumerative sampling technique of all caesarean deliveries from 1st January 2019 to 31st December 2019. Results: Of the total 971 deliveries, 299 had caesarean deliveries which give and overall caesarean rate of 30.79%. Group 5 contributes the maximum number of caesareans (32.44%) followed by group 2 and group 1 contributing 25.75% and 13.04% respectively. Group 3 and group 4 constituted a total of 11.7% of caesarean section in our study. Total breech delivery by caesarean was 25 (7.02%) out of which 21 (84%) were delivered by caesarean section. The rest multiple pregnancy (group 8), abnormal lie (group 9) and preterm (group 10) constitutes 3.01%, 0.67% and 6.35% respectively. Conclusions: In our study, the maximum overall caesarean section rate was contributed by group 5 (32.44%) which was followed by group 2 (25.75%) and group 1(13.04%). So reduction of the primary caesarean sections for primi mothers by following proper induction protocols is needed to reduce the cesarean sections.